MiR-197 Inhibitor Loaded AbCD133@MSNs@GNR Affects the Development of Prostate Cancer Through Targeting ITGAV - Guanqun Ju; Yingjian Zhu; Tao Du; Wanli Cao; Jianhai Lin; Chun Li; Dongliang Xu; Dongliang Xu; Zhijun Wang (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer is one of the most severe male malignant tumors, which ranks second in mortality rate among all tumors. Traditional methods of treatment for prostate cancer produce obvious side effects and a high recurrence rate. Cancer stem cells are considered to be a group of cells that determine the proliferation, metastasis, and drug resistance of tumor. Prostate cancer therapy based on microRNAs and prostate cancer stem cells (PCSCs) has been a research hot spot in this field. Previous studies have reported that miR-197 plays an important role in the occurrence and development of prostate cancer, but the molecular mechanism of miR-197 on the development of prostate cancer has not been reported yet. In this study, we verified that miR-197 is significantly overexpressed in prostate cancer tissues and prostate cancer cells. Then, we verified that miR-197 expression affects the proliferation, invasion, and metastasis of prostate cancer cells by regulating integrin subunit alpha V (ITGAV) expression through STAT5 pathway, and the results indicated that the miR-197 inhibitor can be a prostate cancer suppressor. Then we synthesized the AbCD133@GNR@MSNs@miR-197 inhibitor drug carrier, in which 35.42 μg of the miR-197 inhibitor could be loaded in 1 mg of AbCD133@GNR@MSNs. The AbCD133@GNR@MSNs@miR-197 inhibitor demonstrated good photothermal properties and photothermal controlled-release properties. The modified CD133 antibodies on the surface of the nano drug carrier helped more drug carriers to enter the PCSCs. The pharmacodynamic effects of the AbCD133@GNR@MSNs@miR-197 inhibitor on PCSCs in vivo and in vitro were studied under near-infrared radiation. The results showed that the AbCD133@GNR@MSNs@miR-197 inhibitor prepared in this study could not only significantly suppress the development of PCSCs through ITGAV/STAT5 pathway but also significantly suppress the growth of PCSC solid tumors. In short, our study verified that miR-197 regulates the development of PCSCs through STAT5 pathway by targeting ITGAV, and the AbCD133@MSNs@GNR@miR-197 inhibitor could be a potential suppressor used in prostate cancer treatment. In short, our study found that miR-197 affected the development of prostate cancer by regulating ITGAV. The AbCD133@GNR@MSNs@miR-197 inhibitor prepared in this study could suppress the development and growth of PCSCs in vitro and in solid tumors not only by targeting the ITGAV but also through photothermal therapy. Our study not only provides a theoretical basis for the clinical treatment of prostate cancer but also provides a research scheme of drug loading and microRNA-based photothermal controlled therapy for prostate cancer.